Regulating the global information society - Marsden, Christopher T. (Warwick studies in globalisation., 2000)
An outstanding line-up of contributors explore the regulation of the internet from an interdisciplinary perspective. In-depth coverage of this controversial area such as international political economy, law, politics, economics, sociology and internet regulation. Regulating the Global Information Society covers the differences between both US and UK approaches to regulation and establishes where policy is being made that will influence the future direction of the global information society, from commercial, democratic and middle-ground perspectives.